Analisis Kualitas Pelayanan Kebidanan Pada Ibu Hamil Dengan Risiko Tinggi - Reffita, Lea Ingne (Barongko: Jurnal Ilmu Kesehatan, 2025)
Quality midwifery care is crucial for reducing the risk of complications in high-risk pregnant women. This study aims to analyze the quality of midwifery care for high-risk pregnant women in primary healthcare facilities. The research method used a descriptive quantitative approach, with a survey of 80 high-risk pregnant women receiving care at community health centers (Puskesmas) and regional hospitals. The research instrument was a structured questionnaire that assessed dimensions of midwifery care, including midwife competence, communication, service facilities, and patient satisfaction. Data were analyzed descriptively using frequencies, percentages, and averages. The results showed that the majority of respondents rated midwifery care as good (65%), while 25% rated it as adequate, and 10% rated it as poor. Midwife competence and effective communication are the main factors influencing service quality. Service facilities still need to be improved to support effective examinations and patient comfort. This study concluded that the quality of midwifery care for high-risk pregnant women was generally good, but improvements in facilities and communication are still needed. These findings can inform the development of strategies to improve the quality of midwifery care, particularly for high-risk pregnant women.